First isolation of a new species of Leishmania responsible for human cutaneous leishmaniasis in Ghana and classification in the Leishmania enriettii complex. Issue 11 (September 2015) - Kwakye-Nuako, Godwin; Mosore, Mba-Tihssommah; Duplessis, Christopher; Bates, Michelle D.; Puplampu, Naiki; Mensah-Attipoe, Israel; Desewu, Kwame; Afegbe, Godwin; Asmah, Richard H.; Jamjoom, Manal B.; Ayeh-Kumi, Patrick F.; Boakye, Daniel A.; et al.
Graphical abstract: Highlights: Parasites were isolated from a new focus of human cutaneous leishmaniasis. DNA sequence analysis showed these to be a new species of Leishmania. The parasites belong to the Leishmania enriettii complex. Abstract: An active case detection approach with PCR diagnosis was used in the Ho District of the Volta Region, Ghana that identified individuals with active cutaneous leishmaniasis. Three isolates were successfully cultured and DNA sequences from these were analysed (ribosomal RNA internal transcribed spacer 1; ribosomal protein L23a intergenic spacer; RNA polymerase II large subunit), showing them to be Leishmania, identical to each other but different from all other known Leishmania spp. Phylogenetic analysis showed the parasites to be new members of the Leishmania enriettii complex, which is emerging as a possible new subgenus of Leishmania parasites containing human pathogens.